Talents and virtues: the need to professionalize the civil service in Peru - Rastrollo Suárez, Juan José (2021)
The professionalization of the civil service in Peru has had a remarkable development in the last decades. This process guarantees the proper functioning of the state apparatus, the fight against corruption and the institutional reinforcement. Nevertheless, there are historical conditions that inhibit the development of this necessary process, such as political instability, lack of independence, lack of legal cohesion and inequality.  In this article, the author examines the process of the formation of public bureaucracy in Peru, in its historical context since the country's declaration of independence. Then, he studies the development of public management since the Constitution of 1993, focusing on specific legal norms such as Legislative Decree 728 of 1997, which began the process of ‘laboralization’ of the civil service, or Statute Law 30057 of 2013, which gave birth to the corps of public managers and regulated many competences of the National Authority of the Civil Service. Finally, based on the study of legislation and jurisprudence, the author revises certain key elements for a future reform of public employment in a context of crisis.